A review of literature on Tahfiz Institutions / Nor Tasik Misba and Abd Halim Mohd - Misba, Nor Tasik; Mohd Noor, Abd Halim (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Tahfiz institutions are organizations that specialize in educating students to memorize and recite the whole Al-Quran. The number of Tahfiz institutions in Malaysia has grown from only 58 in 1999 to 1,267 in 2019. These institutions are managed either by the federal government through Islamic Development Department Malaysia (JAKIM), Ministry of Education and state governments under the State Islamic Religious Council (SIRC), or privately owned. There are more than 91% privately owned Tahfiz institutions in Malaysia. These Tahfiz institutions may be owned by foundations, non-government organizations (NGO) or individuals. These Tahfiz institutions may be registered under the Register of Society, state government, and Ministry of Education. Hence, the objective of this article is to analyze the related literature on Tahfiz institutions from 2012 to 2021. Data were obtained from three databases namely Scopus, Web of Science, and Google Scholar. These articles have gone through several processes by considering the inclusion and exclusion criteria stated. A total of 83 articles were analyzed using Atlas.Ti software version 8.0. This study focuses on several variables such as number of articles published per year, research approach, and subject areas covered by the articles. The general findings show that the method of memorizing is amongst the most discussed subject among scholars. Henceforth, this article provides significant suggestions for the future exploration of Tahfiz institutions.